2004
DOI: 10.1088/0268-1242/19/4/069
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulations of III–V MOSFETs

Abstract: The performance potential of an 80 nm physical gate length MOSFET with GaAs channel and high-k gate insulator is investigated using Monte Carlo simulations. The results show that such a device could deliver a 100-125% increase in the drive current at both low and high drain biases compared to equivalent Si based MOSFETs. Various transport model enhancements including the Fermi-Dirac statistics and the interface roughness scattering have been systematically studied in order to attain a more realistic prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…We note that advanced modeling and simulation, such as quantum mechanical Monte Carlo simulation, quantitatively will result in more accurate prediction on such nanodevices [1,7,8]. Modeling interface roughness and scattering gives us an insight into the problems of potential device application.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We note that advanced modeling and simulation, such as quantum mechanical Monte Carlo simulation, quantitatively will result in more accurate prediction on such nanodevices [1,7,8]. Modeling interface roughness and scattering gives us an insight into the problems of potential device application.…”
Section: Discussionmentioning
confidence: 99%
“…The oxide thickness is fixed at 1.2 nm, the doping concentration of channel and substrate is 3 × 10 18 cm −3 , and the doping concentration of the source and drain is 5 × 10 19 cm −3 performance of Si/GaAs MOSFET [14,15]. Simulation by using, such as Monte Carlo approach with a proper quantum mechanical model will provide more accurate estimation on the electrical characteristics of such nanodevices [7,8].…”
Section: Computational Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported simulations of scaled implant free In Ga As MOSFETs have been carried out using our ensemble MC compound semiconductor device simulator MC/MOS described in detail elsewhere [10], [17]. The MC module includes electron scattering with polar optical phonons, inter-and intravalley optical phonons, nonpolar optical phonons, acoustic phonons, and ionized impurities.…”
Section: Monte Carlo Simulation Approachmentioning
confidence: 99%
“…The recent development of a suitable high-gate dielectric for GaAs with a low interface state density [6], [7] has brought the prospects for manufacturable III-V MOSFETs closer to reality [8]. Previous Monte Carlo (MC) simulation studies have shown that 80 nm gate length In Ga As MOSFETs with a conventional surface-channel architecture could outperform by more than a factor of two the equivalent Si and strained Si counterparts [9], [10]. However, when the conventional In Ga As MOSFETs are scaled down to 35 nm, the performance improvement margin shrinks [9], [11].…”
Section: Introductionmentioning
confidence: 99%